1984
DOI: 10.2134/jeq1984.00472425001300030010x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Partitioning of Cadmium, Copper, Nickel and Zinc in Soils and Sediments Containing High Levels of Heavy Metals

Abstract: Three soils and a sediment which had undergone prior massive additions of heavy metals were sequentially extracted so that Cd, Cu, Ni, and Zn could be partitioned into five operationally defined geochemical fractions: exchangeable, bound to carbonates, bound to Fe‐Mn oxides, bound to organic matter, and residual. Metal recoveries were within ± 10% of the independently measured total Cd, Cu, Ni, and Zn concentrations. The highest amount of Cd (ca. 37%) was foand in the exchangeable fraction, and Cu was the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
103
4
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(153 citation statements)
references
References 0 publications
31
103
4
1
Order By: Relevance
“…This is in agreement with Zn associated [31][32]. The present study also shows a comparison of organic bound higher in sequence to exchangeable fraction with studies [27,33], as shown in Fig.…”
Section: Zinc Speciessupporting
confidence: 91%
“…This is in agreement with Zn associated [31][32]. The present study also shows a comparison of organic bound higher in sequence to exchangeable fraction with studies [27,33], as shown in Fig.…”
Section: Zinc Speciessupporting
confidence: 91%
“…This result is consistent with the results of many researchers who found the greatest percentage of nickel in the residual fraction (Gupta and Chen, 1975;Tessier et al, 2002;Hicky and Kittrik, 1984;Ma and Rao, 1997;Moral et al, 2005;Iwegbue, 2007;Chaudhary and Banerjee, 2007;Ogundiran and Osibanjo, 2009;Osakwe, 2010;Iwegbue, 2011). The majority of nickel in soils and sediments is distributed in nature (Gupta and Chen, 1975;Tessier et al, 1980;Hickey and Kittrick, 1984). Norrish (1975) has indicated that nickel is commonly occluded by silicate during soil weathering.…”
Section: Nickelsupporting
confidence: 87%
“…Tessier et al (1979) suggested that metal concentrations in the residual fraction of soils or sediments may be indicative of background metal levels. Heavy metals in the residual (HF-soluble) fraction are propbably associated with silicate minerals (Hickey and Kittrick, 1984). The next important fraction for iron is the carbonate fraction.…”
Section: Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption has been noted as the important control of Copper in soils (Jenne, 1968;Hickey and Kittrick, 1984). The high surface area and adsorbing capacity of Fe-Mn oxide, coupled with the ability of Cu 2+ to replace Fe 2+ in some Fe-oxides (Taylor, 1965) may be responsible for such adsorption.…”
Section: Discussionmentioning
confidence: 99%